Correlation of Rights & Obligations of Citizens & States in Personal Data Protection (Highlighting National Data Hacking Cases) - Sakdiah, Halimatun; Nadiyah, Nadiyah; Ginting, Geby Theresa; Gea, Mayland; Aisyah, Neri; Situmorang, Agtrimas; Harahap, Sanjaya; Ramadhan, Taufiq (QISTINA: Jurnal Multidisiplin Indonesia, 2024)
This study analyzed the incidence of hacking that occurred at the Indonesian National Data Center (PDN) on June 20, 2024, which resulted in a significant disruption to various government services. This study aims to understand the characteristics of cyber attacks, mode operandi ransomware type brainchipper, and the weakness of the security system that causes the leaking of data. By using a descriptive approach and content analysis of various sources, this study has a short and long-term impact of the hacking, including operational damage, a decrease in public trust, and risk to national security. The findings show the importance of reforming the Siber security policy and the strengthening of information technology infrastructure. The study also highlights the responsibility of the government in protecting personal data and providing effective handling of the incident of leaking data to prevent similar events in the future.